A luminescence coordination polymer for long-term monitoring of antibiotic aztreonam in aqueous media. (September 2022) - Liu, Cheng; Chen, Mingyu; Wang, Xiaomei; Ding, Ge; Yang, Tao; Zhou, Xinhui; Xiao, Hongping; You, Yujian
Abstract: The specific recognition and long-term continuously monitoring of antibiotics in water is extremely important for ecosystem and human health. Herein, we report a two-dimensional blue photoluminescence coordination polymer CdL·H2 O (1 ) based on 9 H -carbazole-2, 7-dicarboxylic acid (H2 L), emission of which could be significantly quenched only by aztreonam (ATM) among thirteen antibiotics in aqueous media. By the fluorescence titration experiments, the linear Stern-Volmer plot between emission intensities of 1 and ATM concentrations was observed in the concentration range of 20–100 μM with K sv of 1.12×10 4  M −1 . Besides high selectivity and sensitivity, good anti-interference ability and repeatability for ATM detection were also confirmed. In addition, we immersed 1 into the ATM solution for 60 days, and during this period the fluorescence quenching percentage of ATM for 1 almost unchanged. This result indicates that 1 could be used as a stable high-performance fluorescence sensing material for the specific recognition and long-term continuously monitoring of ATM in water. 1 is also the first fluorescent material that can detect ATM in water. The fluorescence quenching mechanism was attributed to photoinduced electron transfer (PET) from 1 to ATM. Graphical abstract: A 2D coordination polymer CdL·H2 O based on 9 H -carbazole-2, 7-dicarboxylic acid was synthesized. CdL·H2 O could be used as a stable high-performance fluorescence sensing material for the specific recognition and long-term continuously monitoring of aztreonam (ATM) in water. CdL·H2 O is also the first reported fluorescent material that can detect ATM in water. Image 1 Highlights: A luminescence complex 1 shows good selectivity and sensitivity to aztreonam (ATM). 1 could long-term continuously monitor ATM. 1 is the first fluorescent material that can detect ATM in water. The fluorescence quenching mechanism was attributed to photoinduced electron transfer.